Sub-nanoliter metabolomics via mass spectrometry to characterize volume-limited samples - Yafeng Li (Nature Portfolio, 2020)
The analysis of metabolites offers promises in biomarker discovery. Here the authors demonstrate the metabolomics analysis of sub-nanoliter samples using triboelectric nanogenerator inductive nanoelectrospray ionization, which they apply to exhaled breath condensate from cystic fibrosis patients and mesenchymal stromal cells.